A novel approach for laparoscopic retrieval of dermoid cyst - Shah, Nitin H.; Joshi, Aditi V.; Mourya, Sunita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
A dermoid cyst is a germ cell tumour, benign in nature and common in young women under the age of 30. They are usually asymptomatic and often detected incidentally on imaging. Resection of the cyst is important owing to complications like torsion or malignancy. Laparoscopic surgery is the modality of choice in today’s era. However, rupture of the cyst during laparoscopic retrieval is any surgeon’s nightmare. Hence, good surgical skill and a reliable method of retrieval are of prime importance here. Authors present a novel method of dermoid extraction done laparoscopically with a sterile urine collection (urobag) bag. This is an easy and simple method which decreases the rate of spillage owing to the strength of the bag.